Endometriosis and homœopathy - Hunton, Mollie (British Homeopathic Journal, 1993)
8 consecutive patients with endometriosis were followed up from 1 to 4 years to assess the efficacy of homœopathic treatment. All had laparoscopic grading of their endometriosis. All improved with treatment.
Keywords: Endometriosis; Laparoscopy; Infertility; Danazol; Oophorinum; Belladonna; Lachesis